2020
DOI: 10.3390/plants9111621
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvants on Herbicidal Activity and Selectivity of Three Phytotoxins Produced by the Fungus, Stagonospora cirsii

Abstract: The use of many fungal phytotoxins as natural herbicides is still limited because they cannot penetrate leaf cuticle without injury and a little is known on their selectivity. In order to assess the herbicidal potential of phytotoxic 10-membered lactones (stagonolide A, stagonolide K, and herbarumin I), the selection of adjuvants, the evaluation of selectivity of the toxins and the efficacy of their formulations were performed. Among four adjuvants tested, Hasten™ (0.1%, v/v) increased phytotoxic activity of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 59 publications
1
22
0
1
Order By: Relevance
“…The situation was completely different with the adjuvant Hasten. This product is very safe according to safety data sheet information and also possesses no herbicidal activity at typical use concentration up to 1% [ 31 , 49 , 52 , 53 ]. When sprayed on plants, no phytotoxicity symptoms were observed up to the highest tested concentration (5%), which also indicates no own herbicidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…The situation was completely different with the adjuvant Hasten. This product is very safe according to safety data sheet information and also possesses no herbicidal activity at typical use concentration up to 1% [ 31 , 49 , 52 , 53 ]. When sprayed on plants, no phytotoxicity symptoms were observed up to the highest tested concentration (5%), which also indicates no own herbicidal activity.…”
Section: Resultsmentioning
confidence: 99%
“…Herbarumin I (4) inhibited the growth of Amaranthus hypochondriacus seedlings [4] and caused necrotic lesions on sowthistle punctured leaves [10]. In our previous studies stagonolide A (1) and herbarumin I (4) demonstrated the potent post-emergent herbicidal activity against perennial sowthistle aerial shoots, the treatment of plants with these toxins supplemented with Hasten™ led to the development of wide necrotic lesions on the leaf surface [19]. For adequate assessment of future perspectives of most phytotoxic compounds it is important to compare their target activity with that of chemical herbicides.…”
Section: Discussionmentioning
confidence: 99%
“…The final concentration of ethanol was 5% (v/v), the concentration of the tested toxins was 2 mg/mL, 5% EtOH was used as control treatment. Punctured leaf discs of perennial sowthistle (Sonchus arvensis) were placed in a wet chamber and treated with 10 µL of test solutions [19,23]. The diameter of the necrotic lesions was measured 48 and 120 h after treatment.…”
Section: Leaf Puncture Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Adjuvants help to reduce herbicide dose and improve its biological activity by altering the surface tension of spray solution, increasing absorption, translocation rate, effect on atomization, and enhanced penetration ( Hamouda et al, 2021 ). Some adjuvants completely alter the chemical composition of herbicide or even cover the plant surface by keeping the herbicide in contact with plant tissue and hence increase the herbicide penetration and binding ability to kill the target plant without damaging the actual crop ( Dubovik et al, 2020 ). Several studies have demonstrated that adjuvant’s efficacy is dependent on the herbicide being used and the characteristics of the target weed ( Javaid and Tanveer, 2013 ).…”
Section: Introductionmentioning
confidence: 99%